The development of an optimum material selection process for the design of automative brake rotor - Maleque, Md. Abdul; Sarker, Dyuti (2010)
The function of an automotive brake rotor is to slow or stop the motion of a wheel while it runs at a certain speed. The widely used brake rotor material is cast iron which consumes much fuel due to its high specific gravity. In this paper a systematic material selection process using digital logic methods were developed to substitute this cast iron by any other lightweight material. Material performance requirements were analyzed and alternative solutions were evaluated among cast iron, aluminium alloy, titanium alloy, ceramics and composites. Mechanical properties including compressive strength, friction coefficient, wear resistance, thermal conductivity and specific gravity as well as cost, were used as the key parameters in the material selection stages. The analysis led to aluminium metal matrix composite as the most optimum material for brake rotor system. A conceptual design of a brake rotor was developed based on most optimum candidate material.